Problems of declarative and procedural knowledge acquisition for machinery diagnostics - Moczulski, Wojciech (Computer Assisted Methods in Engineering and Science, 2002)
The paper deals with selected problems of knowledge acquisition for intelligent information systems that may be applied for aiding technical diagnostics of machinery and equipment. Two main kinds of knowledge are discussed, i.e. declarative and procedural knowledge. Some methods of declarative knowledge acquisition from domain experts and from databases are presented, the latter being divided into machine learning methods and knowledge discovery ones. Examples of declarative knowledge acquisition and discovery from databases are shown. Moreover, an example of procedural knowledge acquisition from a domain expert is presented. The paper concludes with new issues of knowledge acquisition methodology.